A COMPARATIVE STUDY ON ANTIOXIDANT ACTIVITIES AND PHENOLIC CONTENTS OF FIVE ALGERIAN EGGPLANT CULTIVARS - CHÉRIFA BOUBEKRI; TOUHAMI LANEZ; ASSIA DJOUADI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Total phenolic content and antioxidant activity were measured in the whole fruit of dark-purple eggplant cultivars from five different regions of east Algeria using, respectively, the Folin-Ciocalteu method, spectrophotometrical and electrochemical assays. Total phenolic contents were highest in sample from Jijel, followed by Skikda cultivars, finally sample from Guelma with the lowest phenolic contents. Total phenolic content was positively associated with total antioxidant activity in eggplant extracts. These results demonstrate that phenolic compounds have a significant contribution to the total antioxidant activity, which varies considerably depending on the region of the fruit cultivar analyzed. Antioxidant activity was highly correlated with total phenolic contents (R2 = 0.714).